1986
DOI: 10.1002/j.1460-2075.1986.tb04296.x
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of [125I]ubiquitin to cellular proteins in permeabilized mammalian cells: comparison of mitotic and interphase cells.

Abstract: [125I]Ubiquitin introduced into permeabilized hepatoma tissue culture (HTC) cells rapidly forms conjugates with endogenous proteins. A characteristic pattern of low mol. wt conjugates is obtained which includes the ubiquitinated histone, uH2A, and unknown molecular species with MrS of 14, 23, 26 (two bands) and 29 kd. A broad spectrum of higher mol. wt conjugates is also produced. The formation of all conjugates is absolutely dependent on ATP, and upon depletion of ATP they are rapidly broken down. The 14, 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
(11 reference statements)
1
24
0
Order By: Relevance
“…The proteins were transferred to nitrocellulose filters and immunoblotted as described previously [44]. The anti-(human ubiquitin) antibodies were used at a dilution of lj2000.…”
Section: Immunoblottingmentioning
confidence: 99%
“…The proteins were transferred to nitrocellulose filters and immunoblotted as described previously [44]. The anti-(human ubiquitin) antibodies were used at a dilution of lj2000.…”
Section: Immunoblottingmentioning
confidence: 99%
“…"Ubiquitination" of histones is a postsynthetic and reversible modification that occurs preferentially in actively transcribed regions of chromatin after core particle assembly (20)(21)(22). The level of histone ubiquitination changes as cells progress through the cell cycle or respond to stress (21,23,24). Recently, ubiquitin was also found to be covalently attached to certain cell-surface glycoproteins, especially to lymphocyte-homing receptor (25), and it was suggested that ubiquitination could play an important role in receptor function (26).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin conjugates with molecular masses similar to 28 and 31 kDa have also been observed in Chlamydomonas (Shimogawara and Muto 1989). The 23-and 29-kDa proteins may be ubiquitinated histone 2A and diubiquitinated histone 2A, respectively (Haas and Bright 1985;Raboy et al 1986). Ubiquitin conjugates with molecular masses up to 26 kDa have been observed in the ribosomal fraction (Raboy et al 1986).…”
Section: Discussionmentioning
confidence: 92%
“…The 15-kDa protein is probably a ubiquitin dimer (Haas and Bright 1985;Raboy et al 1986) or a 15-kDa protein of an ubiquitin moiety linked to the C-terminal extension as observed in both Dictyostelium d i s c o i h m and Saccharornyces cerevisiae (Miiller-Taubenberger et al 1988). Ubiquitin conjugates with molecular masses similar to 28 and 31 kDa have also been observed in Chlamydomonas (Shimogawara and Muto 1989).…”
Section: Discussionmentioning
confidence: 96%